2020
DOI: 10.3390/w12041218
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Hydrodynamics of Free Surface Flows in Emergent Vegetated Channels

Abstract: This review paper addresses the structure of the mean flow and key turbulence quantities in free-surface flows with emergent vegetation. Emergent vegetation in open channel flow affects turbulence, flow patterns, flow resistance, sediment transport, and morphological changes. The last 15 years have witnessed significant advances in field, laboratory, and numerical investigations of turbulent flows within reaches of different types of emergent vegetation, such as rigid stems, flexible stems, with foliage or wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 79 publications
1
22
0
Order By: Relevance
“…It must be pointed out that riparian vegetation is very varied and may be broadly divided into rigid/flexible, depending on the mechanical properties of the plant, and emergent/submergent, if the flow depth exceeds the height of vegetation or does not, respectively (e.g., [13,[19][20][21][22][23][24][25][26]). Much research has been devoted to the study of flow-plant interaction in recent years, as demonstrated by the growth of scientific publications dealing with this topic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It must be pointed out that riparian vegetation is very varied and may be broadly divided into rigid/flexible, depending on the mechanical properties of the plant, and emergent/submergent, if the flow depth exceeds the height of vegetation or does not, respectively (e.g., [13,[19][20][21][22][23][24][25][26]). Much research has been devoted to the study of flow-plant interaction in recent years, as demonstrated by the growth of scientific publications dealing with this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrating on emergent vegetation, very recently, Maji et al [26] compiled a comprehensive state-of-the-art, highlighting important research contributions on flow hydrodynamics, including complex interactions between turbulence and vortex structures. Most of the studies have been focused on the investigation of the interaction between flow and vegetation, considering experimental or numerical tests, on a smooth channel bed with staggered-arranged vegetation stems [47,48] or fully and uniformly covered by artificial flexible grass [49,50].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in the mean flow velocity promotes sedimentation, whilst a reduction in contaminant concentration can be achieved through dispersion and bio-chemical degradation. It follows that the detention of contamination, and subsequent bio-chemical degradation, is affected by the reach hydrodynamics (Maji et al, 2020;Persson et al, 1999;Koskiaho, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies of velocity profiles, like those shown in Figures 3-5, are of much interest; in some cases also the shear stress profiles are studied by means of velocity fluctuant components and Reynolds stress theory [19,[107][108][109][110][111].…”
Section: Methodsmentioning
confidence: 99%